Analisis Pendapatan Petani Jagung di Kecamatan Gunem Kabupaten Rembang - Wahyuni, Tri; Setiadi, Agus; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Corn is one of the primary food crop commodities in Indonesia and ranks second in demand after rice. Gunem Subdistrict, located in Rembang Regency, stands out as a major corn-producing area with the largest harvested area, highest production volume, and greatest productivity—covering 5,276 hectares, producing 47,683 tons, and achieving a productivity level of 9.04 tons per hectare. This study aims to analyze the income received by corn farmers and evaluate the level of profitability of corn farming in Gunem Subdistrict. The research was conducted between January and February 2025 using a survey method. Data were collected through direct observation and structured interviews utilizing questionnaires. The sampling technique employed was quota sampling, comprising 90 respondents: 30 farmers each from Suntri, Tegaldowo, and Timbrangan Villages. The data were analyzed using income analysis, Revenue-to-Cost (R/C) ratio, and Net Profit Margin (NPM) analysis. The findings revealed that the average production was 4,789.29 kg per hectare, with an average selling price of Rp3,344.44 per kilogram. The average production cost per hectare per planting season was Rp5,064,107.08, while the average revenue amounted to Rp16,017,493.04 per planting season. Accordingly, the average income earned by corn farmers was Rp10,953,385.95 per planting season. The R/C ratio was 3.16, and the profitability level reached 68.38%, indicating that corn farming in Gunem Subdistrict is economically viable and contributes positively to farmers’ livelihoods.